(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Maize (Zea mays L.) occupied the third place mainly cereal/ fodder produce in the world. Maize gained a chief place in the many cropping pattern of Pakistan. Intercropping is economically beneficial and favorable for the fertility restoration of land. Intercropping of maize with mungbean increased water use efficiency, light use efficiency as well as nutrient use efficiency which positively affect the different yield as well as agronomic parameters like plant height, number of grain row per cob, cobs length, cob girth, thousand grain weight, total dry matter and seed yield which ultimately increases the final yield.